2010
DOI: 10.1007/s11284-009-0685-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of shrubby N‐fixers and non‐N fixers in an arid valley in Southwest China: implications for ecological restoration

Abstract: Shrubs play different key roles in arid regions.Comparisons of shrubs and their site adaptability are essential for correct selection of candidates in developing restoration theory and practice. A survey of topography, soil properties and shrub composition was conducted in fifty-seven 5-m · 5-m plots in an arid valley of the upper Minjiang River, Southwest China. With cluster analysis and critical examinations based on edaphic properties, soil was classified into three groups: dry cinnamon soils (DCS), calcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
(53 reference statements)
2
4
0
1
Order By: Relevance
“…It is worth noting that abundant Ajania nubigena dominated the south-facing slope of Feihong, which had the harshest growing environment that is characterized by moisture and nutrient lacking soil (Table 1). This strong separation of species composition between opposite slopes supports Guan et al 32 www.nature.com/scientificreports/ microphylla as the dominant species with their unique drought-tolerant, nitrogen fixation, and water and soil conservation attributes [44][45][46] . Additionally, drought-tolerant species such as Ajania nubigena and Caryopteris spp.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It is worth noting that abundant Ajania nubigena dominated the south-facing slope of Feihong, which had the harshest growing environment that is characterized by moisture and nutrient lacking soil (Table 1). This strong separation of species composition between opposite slopes supports Guan et al 32 www.nature.com/scientificreports/ microphylla as the dominant species with their unique drought-tolerant, nitrogen fixation, and water and soil conservation attributes [44][45][46] . Additionally, drought-tolerant species such as Ajania nubigena and Caryopteris spp.…”
Section: Discussionsupporting
confidence: 64%
“…For example, Fabaceae represented the largest family in this dry valley, especially with Sophora davidii and Bauhinia brachycarpa var. microphylla as the dominant species with their unique drought-tolerant, nitrogen fixation, and water and soil conservation attributes 44 – 46 . Additionally, drought-tolerant species such as Ajania nubigena and Caryopteris spp.…”
Section: Discussionmentioning
confidence: 99%
“…This species possesses considerable horticultural and evolutionary promise because it flowers continuously throughout the growing season with numerous racemes of showy flowers (Barham, 1997). As a nitrogen fixing species, C. polyantha also plays an important role in the ecological restoration on degraded arid lands (Li et al, 2011a;Song et al, 2010). The shrub only occurs above an elevation of about 1550 m on the valley floor next to the Minjiang River to an elevation of about 2500 m on Jingzhou Hill.…”
Section: Focal Speciesmentioning
confidence: 99%
“…Two greenhouse studies have documented variations in seedling growth, morphology and water use efficiency of Campylotropis polyantha and Bauhinia faberi var. microphylla grown under drought stress (Li et al, 2011a;Song et al, 2010). However, few studies have been conducted to show the effects of elevational changes on leaf functional traits.…”
Section: Introductionmentioning
confidence: 99%
“…The different abilities of both AM fungi ( G. mosseae or G. coronatum) could improve growth on B. faberi seedling, which indicated that it is important and necessary to select beneficial AM fungi for vegetation restoration practice in multi鄄resource limiting regions. [7] 。 小马鞍羊蹄甲( Bauhinia faberi) 是该区域现存植 被中多年生乡土优势灌木之一,在横断山区干旱河谷区域广为分布,具有较强的耐旱特性和优良的水土保持性能,亦可作为饲 料、薪材和药用 [8] ,小马鞍羊蹄甲植被的恢复会产生很好的生态、社会和经济效益,具有巨大的植被恢复潜力。 然而,植被调查 中并未发现其幼苗的大量存在,严酷的干旱环境和贫瘠的土壤可能严重制约了幼苗的定居。 我国退化生态系统中均存在 AM 真菌 [9] ,球曩霉属( Glomus) 是干旱生态系统中分布最广泛 AM 真菌,Glomus mosseae 则是干旱生态系统中的优势 AM 菌种,豆科 植物是其寄生的优势类群 [10] 。 尽管干旱环境条件下小马鞍羊蹄甲对水分和养分胁迫的适应能力已有所研究和揭示 [8,10鄄 11] [13] 描述的方法染色,侵 染率( IR) 采用侵染频度( IF%) 表示,计算公式为:IF% = ( 侵染根段数 / 总根数) 伊 100 [14] ;菌根效应( MGR) 计算公式为:MGR ( %)= ( 菌根植物干重鄄不接种植物干重) / 菌根植物干重伊 100% [15] 3摇 讨论 17] ,并在空间和时间分布上具有强烈的异质性 [11,18] 。 小 马鞍羊蹄甲作为岷江干旱河谷一种优势乡土豆科灌木,其植被生长和空间格局必然受到土壤干旱胁迫和磷分缺乏的共同限 制,。 同时,AM 真菌作为直接联系土壤和植物根系的一类微生物,AM 真菌与植物共生可以改善植物的磷营养,增强植物抵御 干旱的危害,提高植物在逆境中的生存能力 [19]…”
unclassified